2014
DOI: 10.5306/wjco.v5.i3.348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psoralens as anti-tumoral agents in breast cancer cells

Abstract: Core tip: This review examines the biological properties of coumarins by considering their beneficial effects in the prevention of some diseases and as anti-cancer agents. The attention is mainly focused on the effects of psoralens on human breast cancer as they are able to influence many aspects of cell behavior. More recently, it has been reported that these drugs in breast cancer cells are capable of antagonizing some metabolizing enzymes, to affect estrogen receptor stability and to counteract cell invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 94 publications
0
29
0
Order By: Relevance
“…Psoralen has been widely used as a traditional Chinese medicine due to its pharmacological activities, including its anti-tumor 17 , anti-inflammatory 18 , antipyretic and antibacterial activities. The transductional pathways activated by psoralen in target cells are still not well known today.…”
Section: Discussionmentioning
confidence: 99%
“…Psoralen has been widely used as a traditional Chinese medicine due to its pharmacological activities, including its anti-tumor 17 , anti-inflammatory 18 , antipyretic and antibacterial activities. The transductional pathways activated by psoralen in target cells are still not well known today.…”
Section: Discussionmentioning
confidence: 99%
“…Imperatorin significantly upregulates p53 and p21, which subsequently results in Mcl-1 down-regulation and Bax up-regulation in H23 human lung cancer cell [80] and HT 29 colon cancer cells [52] to inhibit their growth. Psoralen upregulates p21, waf and p53 in cells SKBR-3 MCF-7 cells, causing apoptosis [81,82]. Similarly, 5-geranyloxy-7-methoxy coumarin induces apoptosis in SW480 cells through the activation of tumor suppressor gene p53 [72].…”
Section: P53 Modulationmentioning
confidence: 99%
“…On the other hand, their ability to interact with and disrupt DNA replication may represent a starting point to develop anti-cancer agents and therapies based on furanocoumarins [108]. Several in vitro studies have analyzed the inhibitory effects of furanocoumarins on the growth of various cancer cell lines, including breast cancer and non-small cell lung cancer [109,110,111], with psoralen representing a compound commonly employed for the treatment of cutaneous T cell lymphoma in extracorporeal photophoresis, where malignant cells are irradiated with UVA and then reinfused into the subject undergoing the treatment [112]. In recent studies, bergamottin, bergaptol, and bergapten have shown inhibitory effects on breast cancer cell growth.…”
Section: Biological Activities Of Furanocoumarinsmentioning
confidence: 99%